Accessing Specialist Services via Telemedicine in India - Nirupam Bajpai; Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
India is a huge country with a population of diverse social and cultural backgrounds. The majority of its population lives in rural areas. The burden of disease continues to be high in the country with life expectancy at around 68 years, much lower compared to countries in the East Asian region and other advanced economies. As per International Standards, MMR at 130 per 100,000 live births and IMR at 37 per 1,000 live births are high. The public healthcare system in rural areas in India is not only inadequate in terms of population coverage, but is also underutilized due to poor quality of healthcare services. Further, chronic absenteeism of healthcare staff and grossly lacking availability of specialists makes the situation worse. Majority of the population of specialists/doctors live in cities and small towns. Telemedicine can be an ideal solution in such situations. Telemedicine make use of telecommunication technologies which can enable patients in rural areas to get consulted and spoken to by specialists remotely. It can act as a tool to bridge the wide gap in the access to quality healthcare specialsist services between the rural and urban areas. In India, Indian Space Research Organisation (ISRO) is the pioneer in the field of telemedicine. The other key players are the Department of Information Technology (DIT) under Ministry of Communications and Information Technology, Ministry of Health and Family Welfare, Ministry of External Affairs and the state governments. Some of the premier medical institutions and corporate hospitals are also actively involved in the telemedicine activities in India. The present paper gives a detailed account of the telemedicine technology, its importance and various areas of application. The telemedicine initiatives in Indian context are presented in detail. Further, research and development in the field of telemedicine in India is discussed. A brief account of key challenges related to implementation of telemedicine in India are also highlighted.
Keywords: 330; Telemedicine; ICT; Information and Communication Technology; India